Pengaruh Model Kepala Bernomor Struktur Terintegrasi Nilai-Nilai Keislaman terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Febryanti Febryanti; Herlina Ahmad (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
This study aims to determine the effect of the head numbered learning structure model on the material relations and integrated functions of Islamic values on the ability of students to understand mathematical concepts. This research was conducted at the Mega Link Majene Vocational School in class X with a total of 20 students. The research design used is the One Group Pretest Posttest design. The instrument of this research is the concept understanding ability test, observation sheet of student activity and observation sheet of the researcher in the learning process. The results showed that the average pretest score was 50,65 and the average post-test was 82,45 while the normalized N-gain calculation obtained an average increase in student learning outcomes was 0,60 (medium category) and the results of the t-test analysis were obtained. 4,21 with a significance value of 0,000 <α. So it can be concluded that the application of the head learning model with integrated structure with Islamic values can affect the ability to understand students' mathematical concepts.